Comparison Between a Computer-Aided Surgical Template and the Free-Hand Method: A Systematic Review and Meta-Analysis. Issue 6 (December 2019) - Chen, Suya; Ou, Qianmin; Lin, Xuefeng; Wang, Yan
Abstract : Background: During implantation planning, dentists should be able to make an informed decision regarding whether to use an implant template to assist the surgery. Purpose: The aim of this meta-analysis was to assess the results of implantation with or without an implant template based on the accuracy, survival rate, and other considerations. Materials and Methods: In January 2018, a systematic review was undertaken for randomized controlled trials and retrospective and prospective cohort studies with relevance to implant accuracy and the survival rate between the implant template and free-hand method. The odds ratios (ORs) of the survival rate and the mean difference of accuracy deviation from the selected papers were estimated by meta-analysis. Results: Of the 362 screened articles, 6 studies were included in the meta-analysis. Comparison of the survival rate of implant surgery with or without an implant template revealed no significant result (OR = 1.71, 95% confidence interval [CI] 0.65–4.51). Significant differences in accuracy were observed in angular (mean difference = −5.45 degrees, 95% CI −0.66 to −4.24 degrees) and apical deviation (mean difference = −0.83 mm, 95% CI −1.12 to −0.54). Conclusions: With the technology of computer-aided surgical template, implant placement can be more accurate than free-hand operation. No significant difference is observed in the survival rate between template and free-hand.